Rapid Modelling Method and Application using CGA. Issue 4 (August 2021) - Li, Shanglin; Wang, Manli; Ou, Zi; He, Qingwen; Xiao, Juan
Abstract: Creating 3D model Using CGA shaper grammar rules is widely used in the field of rapid building modelling. To create 3D model of Xiangnan University, a set of CGA rules is proposed. These CGA grammar rules include building rules, floor division rules, tile division rule, street rules, roof rules. Finally, in order to test the effect of the model created, the 3D model constructed is imported into Unity3D engine. The final model can be published on multiple platforms such as Web, mobile devices and PC, providing user a free 3D navigation experience.